1975
DOI: 10.1295/polymj.7.300
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Polyethylene. III. Relationships of Microstructure and Thermal Properties

Abstract: ABSTRACT:The thermal properties (viz., second-order transitions, melting points, dynamic and isothermal heat behaviour) of chlorinated polyethylene (CPE) samples are studied here. Thermomechanical analysis (TMA), differential thermal analysis (DTA), and thermogravimetric analysis (TGA) results are listed together to correlate the thermal properties and the microstructure of CPE samples, of various chlorine contents by weight, produced from thermal chlorinated or photochlorinated linear and branched polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A comparative differential thermal analysis of the films and the powder of the CPE samples 8 showed that the structure of the chlorinated products is not affected by these various treatments. The spectra of the films are solventband-free.…”
Section: Methodsmentioning
confidence: 99%
“…A comparative differential thermal analysis of the films and the powder of the CPE samples 8 showed that the structure of the chlorinated products is not affected by these various treatments. The spectra of the films are solventband-free.…”
Section: Methodsmentioning
confidence: 99%
“…!Cl-CH2) triads would appear on the NMR spectra from the beginning of the reaction and not from the 20-25-% chlorine-content interval (Figures 2 and 3). In addition, the thermal CPE samples with chlorine-content value up to 33% still have melting points, 11 which indicates the presence of unchlorinated polyethylene sequences of relatively important lengths. If the chlorineradicals gave -CHCl-units instead of CC1 2 units, there would be 1 -CHCl-unit for 5 -CH2-units in the chain of a 33-% thermal CPE sample; such a product would not keep crystallinity and melting points could not be detected.…”
Section: Injfuence Of the Chlorination Time Up To The Maximum Chlorinmentioning
confidence: 99%